Culture Apparatus for Sea Cucumber Cultivation Having Cleaning Module (2017)
본 발명에 따른 세척 모듈을 갖는 해삼 양식 장치는 해삼이 그 표면에서 생육 상태를 이루게 하는 부착기(10); 및 상기 부착기(10)의 하부에 배치되는 받침대(50);를 포함하며, 상기 부착기(10)에서 떨어져 상기 받침대(50) 상으로 모여진 해삼의 수확 또는 배설물의 청소를 시행하는 것을 특징으로 한다. 본 발명은 해삼의 생육 장소인 바다 및 양식장 등에 설치되는 해삼양식장치를 이루는 부착기 상에 병진 운동하는 세척 모듈을 구비하게 한 상태에서, 상기 세척 모듈을 통해 주기적으로 부착기의 표면을 세척하게 하는 과정을 통해 생육 환경을 최상으로 유지한다. The present invention relates to an apparatus for farming sea cucumbers growing in sea or in fish farms, and more particularly, to an apparatus for farming sea cucumbers enabling collection of the sea cucumbers from an attacher on which the sea cucumbers grow on being disposed under the sea or in fish farms and cleaning of a surface of the attacher as well. According to the present invention, an apparatus for farming sea cucumbers having a cleaning module comprises: an attacher (10) allowing the sea cucumbers to form a growth condition thereon; and a stand (50) placed in the lower part of the attacher (10). The apparatus enables to collect the sea cucumbers dropped from the attacher (10) and gathered on the stand (50), or to clean excrement of the sea cucumbers. According to the present invention, a growing environment can be kept in the best state through a process of periodically cleaning surface of the attachers through the cleaning module in a state that the cleaning module is installed, wherein the cleaning module performs translation motion on the attacher forming a sea cucumber farming apparatus installed in sea and fish farms which are a growing place of the sea cucumbers.